Pengaruh Kompensasi Dan Disiplin Kerja Terhadap Kinerja Karyawan Pertamina Upstream Data Center - Fania Danianti Juwita; Dewi Astuti; Didin Solehudin (PT. Karya Inovatif Nusantara, 2025)
The company must continue to pay attention to the role of its human resources. The attention that can be given by the company can be in the form of compensation and discipline given so that the performance of the employees is also maintained. This study aims to determine the effect of compensation and work discipline on the performance of Pertamina Upstream Data Center employees. The analysis method of this study uses quantitative statistic with data collection techniques through distributing questionnaires and supported by secondary data. The sample in this study were 60 respondents who were employees in the Pertamina Upstream Data Center Digital Data division. The data analysis used was validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, linearity test, multiple linear regression analysis with SPSS 25 data processing. The results of this study indicate that the compensation and work discipline variables partially and simultaneously have a positive and significant effect on the performance of Pertamina Upstream Data Center employees. The employee performance variable can be explained by the compensation and work discipline variables by 78.6%. While the remaining 21.4% is explained by other variables not included in this study.